2017
DOI: 10.1111/jph.12554
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antifungal Activity of Essential oils and Major Components against Fungi Plant Pathogens

Abstract: The indiscriminate use of synthetic fungicides has caused several problems to the environment, which place human and animal health at risk. Due to this fact, the search for natural alternatives to control phytopathogenic fungi growth has increased. This study aims to evaluate the antifungal activity of two essential oils (EOs) and three major components of EOs on the radial growth and spore germination of Fusarium verticillioides and Alternaria tenuissima. Minimum and half‐maximal inhibitory concentrations (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Importantly, EO contain complicated components and show multiple target synergistic effects to exert antipathogen effects, so it is not easy to develop drug resistance (Hou et al, 2022). Furthermore, some constituents occurring in the EO, including carvacrol and thymol (Zhao et al, 2021), viridiflorol, pinocarveol, bornyl acetate, ledol (El Karkouri et al, 2021, citral and geraniol (Loṕez-Meneses et al, 2017), have been found to have antifungal activity. It has been previously reported that many species are important EO sources and have potent antimicrobial effects, such as Allium sativum, Foeniculum vulgare (Li et al, 2022a), Eucalyptus camaldulensis (Gakuubi et al, 2017), and Artemisia annua (Ma et al, 2019), but Sabina chinensis is relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, EO contain complicated components and show multiple target synergistic effects to exert antipathogen effects, so it is not easy to develop drug resistance (Hou et al, 2022). Furthermore, some constituents occurring in the EO, including carvacrol and thymol (Zhao et al, 2021), viridiflorol, pinocarveol, bornyl acetate, ledol (El Karkouri et al, 2021, citral and geraniol (Loṕez-Meneses et al, 2017), have been found to have antifungal activity. It has been previously reported that many species are important EO sources and have potent antimicrobial effects, such as Allium sativum, Foeniculum vulgare (Li et al, 2022a), Eucalyptus camaldulensis (Gakuubi et al, 2017), and Artemisia annua (Ma et al, 2019), but Sabina chinensis is relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In general, strategies that make use of natural substances may be more sustainable, for example, the essential oils. In several cases, the control of phytopathogenic fungi occurs through the direct action of essential oil or/and its components against the fungus (Bhardwaja et al, 2015; Kumar & Kudachikar, 2018; López‐Meneses et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites include saponins, phenols, flavonoids, lignans, alkaloids, terpenes, plant steroids, curcuminoids, flavonoids, and glucosides [6]. These compounds possess biological properties such as detoxifying [7]. The absence of these compounds does not lead to instant death, but rather to the weakening of the organism [8].…”
Section: Introductionmentioning
confidence: 99%